2016
DOI: 10.1080/22201181.2016.1244316
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine in premedication to attenuate the acute hyperdynamic response to ECT: a randomised, double-blind, controlled study

Abstract: The choice of anaesthetic agent for electroconvulsive therapy (ECT) depends on seizure duration, haemodynamic and recovery parameters. The aim of the study was to assess the effects of dexmedetomidine premedication on haemodynamic, seizure duration, recovery characteristics and agitation following ECT. Material and method: 60 patients aged 18-60 years scheduled for ECT were enrolled in the study. Dexmedetomidine (0.5 μg/kg) diluted to 10 ml with 0.9% saline or 10 ml 0.9% saline (control) were infused intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Mean agitation score was less in dexmedetomidine group and duration of convulsion was not different in both groups. In our study, dexmedetomidine also reduced BP, HR, and decreased post-ECT agitation [16]. In 2016, Aksay et al retrospectively analyzed 7 patients who received 178 ECT sessions between 2011 and 2015.…”
Section: Discussionsupporting
confidence: 65%
“…Mean agitation score was less in dexmedetomidine group and duration of convulsion was not different in both groups. In our study, dexmedetomidine also reduced BP, HR, and decreased post-ECT agitation [16]. In 2016, Aksay et al retrospectively analyzed 7 patients who received 178 ECT sessions between 2011 and 2015.…”
Section: Discussionsupporting
confidence: 65%
“…In contrast, the cross-over study from Begec et al [ 5 ], which used a higher dose of dexmedetomidine (1 mcg/kg), reported a significant reduction in hyperdynamic response to ECT. Another randomized controlled trial from Bagle et al [ 15 ] reported a smaller increase in MAP and HR with dexmedetomidine 0.5 mcg/kg compared with saline. A lower dose of dexmedetomidine (0.2 mcg/kg) used in a randomized control trial by Li et al [ 12 ] also produced a significant reduction in HR and MAP compared with saline without altering seizure duration and recovery time.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients may have delayed recovery and delayed discharge based on prolonged Modified Aldrete’s Score and Richmond Agitation-Sedation Score seen in the dexmedetomidine group. In a randomized, double-blind study by Bagle et al, Dexmedetomidine was found to better attenuate the hyperdynamic response commonly seen in ECT with minimal effect on seizure duration or recovery time [ 17 ]. A systematic review and metanalysis was performed by Li et al to identify the effects of using dexmedetomidine in combination with intravenous anesthetics, for ECT, on seizure duration, hemodynamic parameters such as maximum mean arterial pressure (MAP) and heart rate after ECT, recovery time, and post-ECT agitation.…”
Section: Anesthetic Drugs Currently Used During Ectmentioning
confidence: 99%